An outline history of the Japanese drama - Lombard, Frank Alanson (George Allen & Unwin, 1928)
This work not only surveys the history of Japanese drama from its earliest forms through to the 19th century, but also provides sympathetic translations of examples of various forms which have dominated at different periods.